Einsatz analytisch beschreibbarer Geometrien zur Berechnung des Kontaktes zwischen Wälzkörper und Bord in Wälzlagersimulationen - Wirsching, Sven; Schwarz, Sebastian; Tremmel, Stephan (60. Tribologie-Fachtagung 2019, 2019)
A large number of different contact points exist in rolling bearings. The rolling elements interact with the raceway, with the cage or other rolling elements and with the rib or ribs. Depending on the load situation, all these contacts contribute differently to the frictional power, to the temperature increase and thus to the capacity of the bearing. High axial loads are carried by the ribs of roller bearings, as is the case, for example, with tapered roller bearings, but also with the new Angular Roller Unit (ARU) from Schaeffler. In these cases, the contact between the rolling element and the rib significantly influences the frictional power. For its calculation, a detailed description of the contact in bearing simulation tools is necessary. An improved friction calculation allows the specific development of more efficient rolling bearings. In existing programs for the dimensioning of bearings, the contact calculation between rolling element and rib is usually based on the theory of HERTZ, which is accurate only for some geometric pairings. Complex geometries of the contact partners, which are typically used to reduce friction between the rolling element and the rib, cannot be described with sufficient precision, leading to more or less large discrepancies in the calculation of deflections, contact zones and contact pressures compared to high-quality numerical calculations (for example finite element analysis). This also means that the frictional power is not calculated sufficiently accurately. For that reason, this paper presents a new, more accurate method for calculating the contact between the rolling element and the rib. The geometries of the two contact partners are described analytically and form a substitute geometry. By pressing this substitute geometry into a two-dimensional bedding according to the approach of WIN-KLER, the equilibrium of forces in contact is solved similarly to the work of POPOV, whereby the contact area and the resulting pressure distribution are calculated. The developed method is compared for different contact pairings with the finite element method. By comparing the contact area, -shape and -pressure, the potential and the limits of the new method are assessed.
Keywords: Contact; calculation and simulation methods; bearings

Investigations on cage dynamics in rolling bearings by test and simulation - Schwarz, Sebastian; Grillenberger, Hannes; Tremmel, Stephan (74th STLE Annual Meeting & Exhibition, 2019)
Rolling bearing cages perform a very high-frequency movement within their cage pocket clearance compared to the rotational speed under certain operating conditions. This is often accompanied by higher elastic deformation and noise. An unstable cage movement causes high contact forces and reduces the performance of the bearing used. The presentation gives an overview of the essential properties of the unstable cage movement derived by multi-body simulations. Relations between the cage movement and the boundary conditions in the simulation such as coefficient of friction and load are identified. Based on the simulation results, an index is defined that allows the calculated or measured cage movement to be classified into different types and objectively evaluates the cage dynamics. A comparison of the calculated and experimentally measured cage dynamics for different load cases is presented to validate the simulation results.<br

Investigations on the rolling bearing cage dynamics with regard to different operating conditions and cage properties - Schwarz, Sebastian; Grillenberger, Hannes; Tremmel, Stephan; Wartzack, Sandro (IOP Conference Series: Materials Science and Engineering, 2021)
The dynamic behavior of a cage can have a significant influence on the performance and the noise of a rolling bearing. In case of an unstable or high-frequency cage movement, vibrations are transmitted to the adjacent machine elements and the environment, which can influence the operating behavior of the whole system. In addition, a loud noise can often be perceived, which is referred to in the literature as cage rattling or squealing. In this paper, characteristics of different cage movements are investigated using multibody simulations and experimental investigations. For this purpose, essential properties of the fundamentally observable cage movement types "stable", "unstable" and "circling" are presented. The calculated cage dynamics and the type of cage motion are used to show dependencies between the operating conditions and the resulting cage movement such as inner ring rotational speed, bearing load or cage characteristics such as pocket clearance. Based on the simulations, interactions between the input parameters can also be determined. The results are used to identify operation-critical conditions and cage properties that lead to high cage dynamics. Finally, a comparison between the results of the multibody calculations and optical measurements is made. The optical measurements are performed using high-speed cameras. Reference markers fixed on the cage and digital image correlation allow the evaluation of the kinematics as well as the deformation of the cage. These results are compared with the simulation data to ensure a high quality of dynamics simulatio
Keywords: Rolling Bearing; Rolling Bearing Cage Dynamics; Dynamics

Kennzahl zur Identifikation der Wälzlagerkäfigdynamik - Schwarz, Sebastian; Grillenberger, Hannes; Tremmel, Stephan (VDI-Berichte 2348, 2019)
Moderne Wälzlagerungen müssen heute nicht mehr nur hohen Ansprüchen an Lebensdauer und Führungsgenauigkeit genügen, sondern es werden auch minimale Reibungsverluste und Störgeräusche gefordert. Störgeräusche entstehen insbesondere dann, wenn unter bestimm-ten Betriebsbedingungen der Käfig eines Wälzlagers zusätzlich zu seiner Rotation eine über-lagerte, im Vergleich zu seiner Drehzahl sehr hochfrequente Bewegung durchführt, die als Geräuschquelle fungiert und häufig von einer starken Käfigverformung begleitet ist. Dieses Phänomen wird in der Literatur als „Käfiginstabilität“ oder „Käfigrasseln“ bezeichnet. In diesem Beitrag wird anhand zahlreicher Mehrkörpersimulationen die Käfigbewegung in ver-schiedenen Wälzlagern unter unterschiedlichen Betriebsbedingungen systematisch analysiert. Hieraus lassen sich grundsätzliche, verallgemeinerbare Bewegungstypen ableiten. Darauf aufbauend wird eine Methodik präsentiert, die es erlaubt, die in einer Simulation berechnete beziehungsweise in einem Experiment gemessene Käfigbewegung automatisiert und mit ho-her Zuverlässigkeit den zuvor definierten Bewegungstypen zuzuordnen. Diese Methodik er-laubt somit eine objektive Beurteilung der Käfigdynamik.<br
CRIS-Team Scopus Importer:2024-12-16
Keywords: Wälzlager; Dynamiksimulation; Wälzlagerkäfig; Diskriminanzanalyse

Prediction of Rolling Bearing Cage Dynamics Using Dynamics Simulations and Machine Learning Algorithms - Schwarz, Sebastian; Grillenberger, Hannes; Tremmel, Stephan; Wartzack, Sandro (Tribology Transactions, 2021)
Cage instability or highly dynamic cage movement can have a strong influence on the performance of rolling bearings. In addition to very loud and disturbing noises (“squeal”), bearing failure due to cage fracture can occur. This article deals with two topics: the general classification of cage motions and the prediction of application-dependent cage motions to prevent cage instability during operation. The dependencies of the unstable cage movement on the bearing’s load and geometric characteristics of the cage are analyzed using a large number of sophisticated simulations, based on multibody dynamics. To evaluate the cage movements, first a key figure called the “cage dynamics indicator” (CDI) is introduced, which is used to classify the simulation results by means of quadratic discriminant analysis into three types “unstable,” “stable,” and “circling” (= classification of cage motion). Second, a machine learning algorithm trained and tested on the basis of more than 4,000 simulation results enables a time-efficient prediction of the physical correlations between bearing load and cage properties and the resulting cage dynamics (= prediction of cage motion). A comparison of the calculated cage dynamics with the results of an optical measurement of the cage dynamics rounds off this article. This comparison illustrates the high quality of the simulation models and the training data used for machine learning.
Keywords: Wälzlager; Dynamiksimulation; Käfiginstabilität; Digitale Bildkorrelation; Maschinelles Lernen

Use of analytically describable geometries to calculate the contact between rolling element face and rib in bearing simulations - Wirsching, Sven; Schwarz, Sebastian; Tremmel, Stephan (Tribologie und Schmierungstechnik, 2020)
Depending on the load situation, the large number of contact points in rolling bearings contribute differently to the frictional power, temperature development and therefore the operating capacity of the rolling bearing. Under axial load, the contact between the roller and rib in particularly influences the operation and thus the frictional performance of a roller bearing, as it is the case with the new Angular Roller Unit (ARU) from Schaeffler. In existing programs for the dimensioning of rolling bearings, the contact calculation between the rolling element face and rib is usually based on the theory of HERTZ, although this is a simplification for complex geometries. This can lead to discrepancies in the calculation of deflections, contact surfaces and pressure compared to high quality numerical calculations (for example finite element analysis). In this paper a new, more accurate method for calculating the contact between the rolling element face and rib is presented and compared with the finite element method. The geometries are described analytically and form a substitute geometry which is pressed into a two-dimensional bedding following the approach of WINKLER. By means of the equilibrium of forces in the contact, similar to the work of POPOV, the contact area and the resulting pressure distribution can be calculated.<br
Keywords: Contact; pressure; friction; calculation and simulation methods; tapered roller bearings; bearings

Using Machine Learning Methods for Predicting Cage Performance Criteria in an Angular Contact Ball Bearing - Schwarz, Sebastian; Grillenberger, Hannes; Graf-Goller, Oliver; Bartz, Marcel; Tremmel, Stephan; Wartzack, Sandro (Lubricants, 2022)
Rolling bearings have to meet the highest requirements in terms of guidance accuracy, energy efficiency, and dynamics. An important factor influencing these performance criteria is the cage, which has different effects on the bearing dynamics depending on the cage’s geometry and bearing load. Dynamics simulations can be used to calculate cage dynamics, which exhibit high agreement with the real cage motion, but are time-consuming and complex. In this paper, machine learning algorithms were used for the first time to predict physical cage related performance criteria in an angular contact ball bearing. The time-efficient prediction of the machine learning algorithms enables an estimation of the dynamic behavior of a cage for a given load condition of the bearing within a short time. To create a database for machine learning, a simulation study consisting of 2000 calculations was performed to calculate the dynamics of different cages in a ball bearing for several load conditions. Performance criteria for assessing the cage dynamics and frictional behavior of the bearing were derived from the calculation results. These performance criteria were predicted by machine learning algorithms considering bearing load and cage geometry. The predictions for a total of 10 target variables reached a coefficient of determination of R2≈0.94" role="presentation">R2≈0.94 for the randomly selected test data sets, demonstrating high accuracy of the models.
Keywords: Wälzlager; Maschinelles Lernen; Käfiginstabilität; Künstliche neuronale Netze; Random Forest; Gradient Boosting; Evolutionäre Algorithmen